Microscopy and biomimetics: the NanoSuit® method and image retrieval platform. (24th December 2021) - Hariyama, Takahiko; Takaku, Yasuharu; Kawasaki, Hideya; Shimomura, Masatsugu; Senoh, Chiyo; Yamahama, Yumi; Hozumi, Atsushi; Ito, Satoru; Matsuda, Naoto; Yamada, Satoshi; Itoh, Toshiya; Haseyama, Miki; et al.
Abstract: This review aims to clarify a suitable method towards achieving next-generation sustainability. As represented by the term 'Anthropocene', the Earth, including humans, is entering a critical era; therefore, science has a great responsibility to solve it. Biomimetics, the emulation of the models, systems and elements of nature, especially biological science, is a powerful tool to approach sustainability problems. Microscopy has made great progress with the technology of observing biological and artificial materials and its techniques have been continuously improved, most recently through the NanoSuit ® method. As one of the most important tools across many facets of research and development, microscopy has produced a large amount of accumulated digital data. However, it is difficult to extract useful data for making things as biomimetic ideas despite a large amount of biological data. Here, we would like to find a way to organically connect the indispensable microscopic data with the new biomimetics to solve complex human problems.